A novel antibacterial biomaterial mesh coated by chitosan and tigecycline for pelvic floor repair and its biological performance. Issue 5 (2nd September 2020) - Liang, Changyan; Ling, You; Wei, Feng; Huang, Lijie; Li, Xiaomao
Abstract: The biomaterials composed of mammalian extracellular matrix (ECM) have a great potential in pelvic floor tissue repair and functional reconstruction. However, bacterial infection does cause great damage to the repair function of biomaterials which is the major problem in clinical utilization. Therefore, the development of biological materials with antimicrobial effect is of great clinical significance for pelvic floor repair. Chitosan/tigecycline (CS/TGC) antibacterial biofilm was prepared by coating CS/TGC nanoparticles on mammalian-derived ECM. Infrared spectroscopy, scanning electron microscopy, bacteriostasis circle assay and static dialysis methods were used to characterize the membrane. MTS assay kit and DAPI fluorescence staining were used to evaluate cytotoxicity and cell adhesion. The biocompatibility was assessed by subabdominal implantation model in goats. Subcutaneous antimicrobial test in rabbit back was used to evaluate the antimicrobial and repairing effects on the infected wounds in vivo . Infrared spectroscopy showed that the composite coating had been successfully modified. The antibacterial membrane retained the main structure of ECM multilayer fibers. In vitro release of biomaterials showed sustained release and stability. In vivo studies showed that the antibacterial biological membrane had low cytotoxicity, fast degradation, good compatibility, anti-infection and excellent repair ability.